Catechol Moiety Integrated Tri‐Aryl Type AIEgen for Visual and Quantitative Boronic Acid Detection. Issue 3 (23rd November 2021) - Hu, Renjian; Lin, Shiyun; Wang, Mengshi; Li, Ruoxin; Shuai, Zhigang; Wei, Yen
Abstract: Novel functional AIEgen based on three compact bound aryl skeletons is designed and synthesized. This tri‐aryl type luminogen (TA‐Catechol) embedded with catechol moiety responds rapidly to series of boronic acids. Real‐time visual and quantitative dual‐mode detection method is established for the first time with modest precision and low detection limit (8.0 μM). Detailed mechanistic discussion identifies tetra‐coordinated boronic species as the key intermediate within sensing procedure. Wide range of organic boronic acids compatible with this strategy is displayed which is promising in high throughput screening technology. Furthermore, solid‐state sensing capability of TA‐Catechol is also demonstrated. Abstract : Double feature : Functional AIEgen TA‐Catechol with dual‐mode detection capability towards series of boronic acids is presented. Photoluminescent properties of TA‐Catechol are studied thoroughly both experimentally and theoretically. Detection performance is estimated for visual and quantitative mode while formation of tetra‐coordinated boronic compound is confirmed to dominate the sensing procedure. Solid‐state recognition and potential applications are discussed.